KEBIJAKAN PENDIDIKAN KHALIFAH AL-MA’MUN DAN IMPLIKASINYA TERHADAP KEMAJUAN ILMU PENGETAHUAN - Munjahid, Munjahid (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
This paper aims to determine the education policy of al-Ma’mun’s caliph and how the implications for the progress of science in education. Al-Ma’mun’s caliph was the golden peak of Muslims. Not only is the safety and comfort of a well-controlled society, but also education and science at that time are growing and developing rapidly. Its is evidenced by the movement to translate books in foreign languages, the writing of original works, the provision of libraries, the establishment of educational institutions, scientifiec research and discussion. Not only that, scientific progress achieved at that time was the growth and development of scientific and educational institutions (such as: Bait al-Hikmah, observatories, the growth of low, middle and high level educational institutions), the development of various scientific disciplines, (such as: astronomy, mathematics, medicine, pharmacy, geography, al-Qur'an, Hadith, kalam science, history and literature). Keywords: policy, science, rational, Mu’tazilah